Entrepreneurial Survey in Relation to Commercial Banks’ Lending - H S, Anitha (Ushus Journal of Business Management, 2005)
Entrepreneurship in India, even today, is the prerogative of certain sections of the society. These classes are the major beneficiaries of entrepreneurial schemes and programmes of the government and financial institutions. It has been proved time and again that those who have come from trade and industrial backgrounds get easy access to non-institutional finance, but those who have come from a professional background mainly depend on institutional finance. Sadhak found that entrepreneurs who were formerly traders had better access to financial resources than technocrat/professional entrepreneurs. Manohar V. Deshpande found that the institutional agencies such as IDBI, SFCs and commercial banks, created by the government to help prospective entrepreneurs were not successful in developing entrepreneurs from all castes in the Marathwada region of Maharashtra state.